Group Counseling with Modeling Techniques to Increase Vocational High School Students' Learning Motivation - Komang Silvia Angelia; Dewi Arum Widhiyanti Metra Putri; Luh Putu Sri Lestari (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Many students do not have motivation and discipline in the learning process, including students who do not want to complete their assignments on time, like to procrastinate and procrastinate, do not want to complete their assignments, do not focus on carrying out the learning process and even tend to be very lazy. This study aims to analyze the effectiveness of cognitive behavioral counseling with cognitive restructuring techniques to improve learning discipline and learning motivation. The research design used is a pretest-posttestnonequivalent control group design. The data collection methods used by the researcher include questionnaires, observation methods, and interview methods. In this study, the normality test was carried out with the Shapiro wilk normality test with the help of SPSS 23.0 for Windows. The hypothesis test conducted with MANOVA is the result of a multivariate test on Wilks' Lambda informing that the F value is 2.963. To determine the effectiveness of the treatment given, the size effectiveness (ES) formula is used, while the result of the calculation of size effectiveness (ES) is 0.408. When viewed based on the criteria for the level of effectiveness in the effect size test, which is 0.2< ES ≤ 0.8 is categorized as moderate or quite effective. So it can be concluded that cognitive counseling with simultaneous cognitive restructuring techniques is quite effective in improving learning discipline and student learning motivation.